Policy Study of Local Content Curriculum in Madrasah - Abdullah Muwaffaq; Iksan Iksan (EduLine: Journal of Education and Learning Innovation, 2023)
The local curriculum that is part of the national curriculum has educational programs. One of the elements that must be maintained and maintained through educational activities is the values, traditions, culture, skills, and concepts prevailing in society. In recent years, the government implemented curriculum changes by adding local subjects. Through learning local subjects, it is expected that students will not only have academic knowledge that is global as expected but also have concern for social and cultural values that surround students. Researchers use the literature study method, which is a method of collecting data by understanding and studying theories from various literature related to the research. There are four stages of literature study in this research, namely preparing the necessary equipment, compiling a bibliography, managing time, and reading or recording research material. Conceptually, the locally-based curriculum consists of two forms. The first form is inherent in all subjects, and the second form is a separate activity that is not related to the subject. This paper tries to explain the model and implementation of a locally-based curriculum in Madrasah